2012
DOI: 10.1016/j.ajog.2012.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alcohol, lithium, and homocysteine on nonmuscle myosin-II in the mouse placenta and human trophoblasts

Abstract: Mouse embryonic exposure to alcohol, lithium, and homocysteine results in intrauterine growth restriction (IUGR) and cardiac defects. Our present study focuses on the placental effects. Objectives We analyzed the hypothesis that expression of nonmuscle myosin (NMM)-II isoforms involved in cell motility, mechanosensing, and extracellular matrix assembly, are altered by the three factors in human trophoblast (HTR8/SVneo) cells in vitro and in the mouse placenta in vivo. Study Design After exposure during gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…For venous hemodynamics, we used the presence of flow reversal during atrial contraction (A wave) in the ductus venosus and the presence of umbilical venous pulsations. The abnormal echocardiographic patterns relating to myocardial and valve defects have been published [17, 18]. Our research indicates that the observed cardiac defects are preventable with folate supplementation that is initiated early after conception and at higher doses than presently available in periconceptional vitamins.…”
Section: Cardiac Birth Defectssupporting
confidence: 51%
See 3 more Smart Citations
“…For venous hemodynamics, we used the presence of flow reversal during atrial contraction (A wave) in the ductus venosus and the presence of umbilical venous pulsations. The abnormal echocardiographic patterns relating to myocardial and valve defects have been published [17, 18]. Our research indicates that the observed cardiac defects are preventable with folate supplementation that is initiated early after conception and at higher doses than presently available in periconceptional vitamins.…”
Section: Cardiac Birth Defectssupporting
confidence: 51%
“…Two important pathways critical to placental development, implantation, and cardiac development during the same period of early development are canonical Wnt/ β -catenin signaling and pathways associated with folate metabolism [1721]. If these pathways are altered, developmental anomalies ensue.…”
Section: Environmental Influencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Decreased DNA methylation has been reported in one of the differentially methylated regions of the Igf2 locus in prenatally alcohol-exposed mice. Finally, mouse embryonic exposure to alcohol, lithium and homocysteine results in IUGR and cardiac defects by alteration of expression of nonmuscle myosin-II isoforms involved in cell motility, mechanosensing and extracellular matrix assembly [55]. Furthermore, alterations of proteins with roles in cellular function, cell cycle, and the ubiquitin-proteasome pathway induced by alcohol have recently been demonstrated [54].…”
Section: Alcohol Consumption and Tobacco Smokingmentioning
confidence: 99%